THE INFLUENCE OF WORK ENVIRONMENT AND COMPENSATION ON EMPLOYEE TURNOVER INTENTION WITH SATISFICATION AS A MODERATING VARIABLE - Sono, Moh Gifari; Annisa, Sri; Mubayyin, Muhammad Afief; Karyono, Septin Maisharah; Mardiah, Ainil (ITB AAS Indonesia Surakarta, 2024)
Abstract The existence of employees in a company is the most important thing for the company to be able to achieve its targets and vision well, so employee turnover must be avoided in any way and under any circumstances. There are a number of factors that can reduce employee turnover intention, including a good work environment and adequate compensation for employees. This research is a quantitative research with an explantory approach. The data used in this research is secondary data obtained from the questionnaire method of 250 BCA Syari'ah bank employees spread throughout Indonesia including KC BCA Syari'ah Medan, KC BCA Syari'ah Palu, KC BCA Syari'ah Bojonegoro, KC BCA Syari'ah Makasar, and KCP Bank Syari'ah Central Jakarta. The research results show that the Work Environment and Compensation variables have a negative relationship and a significant influence on the Employee Turnover Intention variable. Apart from that, the job satisfaction variable is able to moderate the two hypotheses above. Keywords: Compensation, Work Environment, Job Satisfication, Employee Turnover Intention